Academic Student Disengagement in Arabic Language Learning in the Digital Age: A Studynon the Low Utilization of Digital Learning Media at STAI NU Kotabumi, Lampung - Zalila, Nur; Hidayat, Nur; Syafitri, Meli; Mizlan, Mizlan; Zaini, Muhammad (Jurnal Ragam Pengabdian, 2026)
This study explores the phenomenon of student academic disengagement in Arabic language learning in the digital age by examining its relationship with the limited use of digital learning media at STAI NU Kotabumi, Lampung. The study addresses low student engagement, reflected in minimal classroom participation, limited academic interaction, and declining motivation resulting from predominantly conventional teaching practices. A qualitative case study approach was employed involving two Arabic language lecturers and five students selected through purposive sampling. Data were collected through observations, in-depth interviews, and documentation and analyzed using the Miles and Huberman interactive model. The findings reveal that limited utilization of digital learning media contributes to students’ academic disengagement, which is manifested in low classroom participation, weak academic interaction, reduced learning motivation, and limited enthusiasm for completing learning tasks. Arabic language instruction remains largely dependent on PowerPoint presentations and messaging applications, resulting in a monotonous learning environment that does not adequately support active student engagement. The novelty of this study lies in demonstrating how inadequate integration of digital learning media is associated with academic disengagement in Arabic language learning within the context of an Islamic higher education institution. These findings highlight the need to develop more interactive and technology-based Arabic language learning strategies to strengthen students' behavioral, emotional, and cognitive engagement.